COMPONENTS OF THE CURRICULUM - Nurhul Syadikin (Review of International Journal Education and School Leadership, 2024)
A curriculum in a broad sense is defined as a teaching program at an educational level. Whereas in the narrow sense, it is a subject for several hours of lessons. The curriculum design must fulfill two requirements, namely (1) conformity between the curriculum and the demands, needs, conditions, and development of society; (2) compatibility between curriculum components, namely the content according to the objectives, the process according to the content and objectives. The sources of making a curriculum consist of science, society, immortality and divinity, knowledge, and learners. The considerations that underlie the making of a curriculum design are scope, sequence, continuity, integration, articulation, and balance. The curriculum component consists of four elements, namely the objective component, the teaching material component, the strategy component, and the evaluation component.